Manajemen Kepala Sekolah Dasar Islam dalam Mengembangkan Pendidikan Karakter Religius di Era Disrupsi (Studi kasus di SD Islam Al Rasyid Kota Pekanbaru) - Muslim Muslim; Yusnimar Yusri; Syafaruddin Syafaruddin; Mahyudin Syukri; Wismanto Wismanto (Departement of Mathematics Education, 2023)
This study aims to find out how the management of Islamic Elementary School Principals is in fortifying and at the same time growing and developing religious character education in the digital era. This study uses a qualitative method. The principal of al-Rasyid Pekanbaru Islamic Elementary School became the main sample in this study. Data collection techniques used interviews, observation and documentation, analysis of research data using reduction techniques, triangulation and conclusions from research data. Based on this research, it was concluded that the management of Islamic elementary school principals in developing religious character education in the era of disruption by prioritizing the psychological side of students which has implications for behavior, character building in children is carried out to create students who have good knowledge and behavior. The character of students should have values originating from the Qur'an and Sunnah, so that their religious character can emerge and develop properly, then we will apply the values contained in Pancasila education, religion, culture, and the goals of national education, namely honest, tolerant, religious, disciplined, cooperative, creative, democratic, independent, national spirit, curiosity, love of the motherland, friendly, communicative, respect for achievement, love peace, care for the environment, love to read, care socially, and be responsible. Student religiosity is shown by obedient attitudes or behavior in carrying out the teachings of the religion that has been adhered to, tolerant of the implementation of religious worship and living in harmony with adherents of other religions. The results showed that the management of the head of Al Rasyid Pekanbaru Islamic Elementary School in fostering religious character education was going well with very good planning, organizing, implementing and evaluating. Information technology helps facilitate all human activities, information search, information delivery and literacy about adding knowledge in learning by utilizing technology, so that students can learn by making the most of learning resources.